Deviation Of Marriage Age Issues in Indonesia (Integration Review of Maqashid Sharia and Positive Law) - Nurul Aini Octavia; Wardatun Nabilah; Martia Lestari (Faculty of Sharia, Institut Agama Islam Negeri (IAIN) Metro, Lampung, Indonesia., 2023)
This research will answer two research questions, first: what are the rules regarding marriage dispensation in Indonesia and secondly, how is the problem of